2021
DOI: 10.3390/nano11092406
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Evaluation of Gold Nanoparticles Functionalized with Thiol Ligands for Robust Radiolabeling with 99mTc

Abstract: Radiolabeled gold nanoparticles (AuNPs) have been widely used for cancer diagnosis and therapy over recent decades. In this study, we focused on the development and in vitro evaluation of four new Au nanoconjugates radiolabeled with technetium-99m (99mTc) via thiol-bearing ligands attached to the NP surface. More specifically, AuNPs of two different sizes (2 nm and 20 nm, referred to as Au(2) and Au(20), respectively) were functionalized with two bifunctional thiol ligands (referred to as L1H and L2H). The sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…It is of major importance that nanoparticles aiming to serve as theranostic agents have minimal interactions with blood components so as not to compromise their systemic administration. To this end, nanosystems such as iron oxide or gold nanoparticles must prove their biocompatibility before being intravenously injected into a living organism [ 61 , 62 ]. In our case, all samples exhibited minimal hemoglobin release from the RBCs, indicating negligible hemolysis according to the <10% acceptance limit for biopharmaceuticals [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is of major importance that nanoparticles aiming to serve as theranostic agents have minimal interactions with blood components so as not to compromise their systemic administration. To this end, nanosystems such as iron oxide or gold nanoparticles must prove their biocompatibility before being intravenously injected into a living organism [ 61 , 62 ]. In our case, all samples exhibited minimal hemoglobin release from the RBCs, indicating negligible hemolysis according to the <10% acceptance limit for biopharmaceuticals [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Radioactive metals such as 99m Tc ( T 1/2 = 6 h, E y = 140 keV) and 188 Re ( T 1/2 = 17 h, E y = 2.12 MeV, penetration distance = 3.8 mm) are widely used in clinical practice for diagnostic and therapeutic purposes. , 99m Tc is a diagnostic γ emitter and can be detected by SPECT-CT, while 188 Re is a therapeutic β emitter and has great therapeutic potential for internal radiotherapy. According to previous works, SnCl 2 is generally used as a reducing agent for the radiolabeling of NPs and is usually added to [ 99m Tc]­TcO 4 – or [ 188 Re]­ReO 4 – solutions. The radiolabeling protocol of the developed NPs was optimized for 188 Re.…”
Section: Resultsmentioning
confidence: 99%
“…Τhe synthesis and characterization of the AuNPs and the thiol ligand (Figure 1) have been previously described [23]. Both samples were prepared according to the same procedure, during which 500, 500 × 10 −1 , 500 × 10 −2 and 500 × 10 −3 µg of AuNPs were each mixed with 0.29 mg of the ligand previously dissolved in DMSO and allowed to stay overnight on a magnetic stirrer.…”
Section: Functionalization Of Gold Nanoparticles With a Thiol Trident...mentioning
confidence: 99%
“…Cytotoxicity studies were performed following a previously reported procedure using the 4T1 cancer cell line [23]. Cell viability of bare AuNPs and ligand-functionalized AuNPs was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay.…”
Section: Cell Viability By Mtt Assaymentioning
confidence: 99%
See 1 more Smart Citation